2002
DOI: 10.1002/ajmg.10533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiple presenilin 2 SNPs for association with early‐onset sporadic Alzheimer disease

Abstract: The presenilin genes encode proteins that modify, mediate, or perform similar functions to gamma-secretase, the enzyme responsible for converting amyloid beta precursor protein (APP) into beta-amyloid. Mutations in the presenilin genes cause an increased production of Abeta42, the aberrant form of beta-amyloid found in the neural plaques of Alzheimer disease patients. Previously reported association studies of presenilin 2 (PSEN2) polymorphisms with early-onset Alzheimer disease (EOAD) have produced contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Another possible explanation is that βand γ-secretases in AD brain may have intrinsic sensitivity to cholesterol and therefore low cholesterol levels are needed to stimulate their activities. Single nucleotide polymorphisms (SNP) in genes encoding γ-secretase components modify AD risk (Yasuda et al, 1999;Dermaut et al, 2002;Howell and Brookes, 2002). Whether any SNP affects secretase sensitivity to cholesterol requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that βand γ-secretases in AD brain may have intrinsic sensitivity to cholesterol and therefore low cholesterol levels are needed to stimulate their activities. Single nucleotide polymorphisms (SNP) in genes encoding γ-secretase components modify AD risk (Yasuda et al, 1999;Dermaut et al, 2002;Howell and Brookes, 2002). Whether any SNP affects secretase sensitivity to cholesterol requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Replication studies of the SNP rs8383 have been previously performed [ 5 , 29 ]. The abovementioned meta-analysis for rs8383 showed that the polymorphism is associated with a heightened risk of AD [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recessive genetic model, however, did not a yield statistically significant association between the C allele and AD (CC vs. TT+TC: OR=1.14, 95% CI=0.93-1.41). In the subtype analysis by APOE ε4 allele status using the available data (Combarros et al, 1999;Howell and Brookes, 2002;Singleton et al, 1997), significant association was found in the recessive genetic model for the APOE ε4 positive contrasts (OR=2.40, 95% CI=1.22-4.71). However, the APOE ε4 negative contrasts did not yield statistically significant (Table S1).…”
Section: Rs8383 Polymorphismmentioning
confidence: 92%
“…1, Tables 1 and 2) published from 1997 to 2009 (Brookes et al, 1997;Combarros et al, 1999;Giedraitis et al, 2009;Howell and Brookes, 2002;Prince et al, 2001;Singleton et al, 1997). The sample sizes of the AD case group ranged from 81 to 202 and the number of controls ranged from 78 to 383.…”
Section: Rs8383 Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation